2019
DOI: 10.1097/fjc.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Bisoprolol in Patients With Acute Coronary Syndrome

Abstract: To date, many questions about the extent and cause of pharmacokinetic (PK) variability of even the most widely studied and prescribed β1-adrenergic receptor blockers, such as metoprolol and bisoprolol, remain unanswered. Given that there are still no published population pharmacokinetic (PopPK) analyses of bisoprolol in routinely treated patients with acute coronary syndrome (ACS), the aim of this study was to determine its PK variability in 71 Serbian patients with ACS. PopPK analysis was conducted using a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Clinically relevant serum concentration of BIS was recently reported to range between 3.8 and 71.1 ng/mL (or 0.011 and 0.22 µM) [46]. These values are similar to the IC 50 required for its suppression of I K(M) presented herein.…”
Section: Discussionsupporting
confidence: 83%
“…Clinically relevant serum concentration of BIS was recently reported to range between 3.8 and 71.1 ng/mL (or 0.011 and 0.22 µM) [46]. These values are similar to the IC 50 required for its suppression of I K(M) presented herein.…”
Section: Discussionsupporting
confidence: 83%
“…Bisoprolol does not show on the lists as P-gp or CYP3A4 inhibitor but is known to be metabolized partly by CYP3A4 (and partly by CYP2D6). [57][58][59][60] The specific interactions of dabigatran with verapamil, and rivaroxaban with verapamil or amiodarone, are consistent with previous reports in animal models 61 and in humans. 46,[62][63][64][65] Verapamil increased dabigatran exposure in real life.…”
Section: Discussionsupporting
confidence: 90%
“…Amiodarone exact strength of inhibition is still "yet to‐be‐determined" in the published lists 14 . Bisporolol, is known to be metabolized partly by CYP3A4 (and partly by CYP2D6) 57–60 . Amlodipine had been shown to affect P‐gp mediated transport, and is not a CYP3A4 inhibitor 31,32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a previous study has shown that smoking has a significant effect on bisoprolol clearance, possibly due to induction of CYP3A4. 23 Women have higher drug exposure and lower clearance of metoprolol, 24 but the influence of sex in the pharmacokinetics of bisoprolol has not been studied. The typical clearance estimated in our population was 13.1 L/h.…”
Section: Discussionmentioning
confidence: 99%